Spatial distribution of zooplankton in the Beagle Channel in relation to hydrographic and biological drivers in different seasons - Valencia Carrasco, Laura Constanza; Boy, Claudia Clementina; Malits, Andrea; Martín de Nascimento, Jacobo; Capitanio, Fabiana Lia (Journal of Marine Systems)
This study aimed to evaluate the spatial distribution and seasonal variability of zooplankton, mainly copepod groups, along the Beagle Channel (BC), an interoceanic passage at the southernmost tip of South America. We focused on the Argentine part of the BC, which comprises an inner sector under a strong continental influence and an outer sector influenced by offshore sub-Antarctic waters, separated by the narrow Mackinlay Strait. We analyzed zooplankton samples collected with 67 μm- and 200 μm-mesh nets in the inner and outer sectors of the BC during different seasons from 2014 to 2018, along with oceanographic parameters, total chlorophyll a (Chl a) concentration, and microbial community composition. Results showed a seasonal pattern, where zooplankton abundance was highest during spring and summer, with the largest-sized calanoid copepods being dominant in the inner sector in spring and in the outer sector in summer, and lowest in autumn and winter, small calanoid copepods being dominant in winter. Calanoid and cyclopoid copepodites and copepod nauplii were more abundant in spring and summer than in the other seasons. Conversely, adults of both groups were predominant in autumn and winter. The variables that better explained the abundance of the main copepod groups were Chl a concentration, picoeukaryotes abundance, and, to a lesser extent, water column stratification. Our findings suggest the existence of two seasonal patterns in the mid-eastern BC: a classical herbivore food web in spring-summer under high phytoplankton biomass, where the presence of larger copepods is associated with higher trophic levels, and a microbial food web in autumn-winter, with low phytoplankton biomass, characterized by great dominance of picoplankton that supports the grazing of the smallest copepods. Fil: Valencia Carrasco, Laura Constanza. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Biodiversidad y Biología Experimental y Aplicada. ...